Victor D. Hansol (Ed.). Hoplites: The Classical Greek Battle Experience, (London-New York), Routledge, 1991. 286 pp - Fornis, César; CASILLAs, Juan Miguel (Gerión. Revista de Historia Antigua, 1992)
Sin resumen